2004
DOI: 10.1042/bj20040735
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of dimerization and substrate phosphorylation inhibit factor inhibiting hypoxia-inducible factor (FIH) activity

Abstract: HIF (hypoxia-inducible factor) is an alphabeta transcription factor that modulates the hypoxic response in many animals. The cellular abundance and activity of HIF-alpha are regulated by its post-translational hydroxylation. The hydroxylation of HIF is catalysed by PHD (prolyl hydroxylase domain) enzymes and FIH (factorinhibiting HIF), all of which are 2-oxoglutarate- and Fe(II)-dependent dioxygenases. FIH hydroxylates a conserved asparagine residue in HIF-alpha (Asn-803), which blocks the binding of HIF to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 49 publications
1
61
0
3
Order By: Relevance
“…For example, phosphorylation of hHIF-1a at Thr796 by casein kinase II was first postulated by Gradin et al 51 , and substitution of an aspartic acid residue at this position to mimic phosphorylation increased the interaction of the CAD with p300 within cells. It was subsequently shown that a peptide phosphorylated at this position could not be hydroxylated by FIH-1, 52 and the aspartic acid mutation significantly decreased hydroxylation efficiency in vitro. 53 Finally, in vitro interaction assays demonstrated that phosphorylation alone at this position did not enhance binding to p300, 41 and rather indicated that phosphorylation at Thr796 inhibited hydroxylation by FIH-1, facilitating increased p300 binding and CAD activity.…”
Section: Other Modifications Affecting Hif-driven Transcriptionmentioning
confidence: 99%
“…For example, phosphorylation of hHIF-1a at Thr796 by casein kinase II was first postulated by Gradin et al 51 , and substitution of an aspartic acid residue at this position to mimic phosphorylation increased the interaction of the CAD with p300 within cells. It was subsequently shown that a peptide phosphorylated at this position could not be hydroxylated by FIH-1, 52 and the aspartic acid mutation significantly decreased hydroxylation efficiency in vitro. 53 Finally, in vitro interaction assays demonstrated that phosphorylation alone at this position did not enhance binding to p300, 41 and rather indicated that phosphorylation at Thr796 inhibited hydroxylation by FIH-1, facilitating increased p300 binding and CAD activity.…”
Section: Other Modifications Affecting Hif-driven Transcriptionmentioning
confidence: 99%
“…The region between residues 223 and 233 appears to extend from a long loop between DSBH ␤-strands IV and V (␤-9 and ␤-10) and probably serves to enclose the active site. The region between residues 303 and 318 is located prior to the C-terminal helix, which for some 2OG oxygenase family members has been shown to play a role in substrate recognition (56); in FIH, the C-terminal helices are involved in dimerization in addition to substrate recognition (57). Assuming the structure of PAHX as observed represents an "open" conformation with its disordered loops, a large groove leading to the active site is clearly visible on its surface.…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, it has also been reported that Thr-796 in the C-TAD of HIF-1␣ might be phosphorylated because its mutation to alanine strongly reduced the transcriptional activity of HIF-1␣ (22). It is likely that phosphorylation of this residue, by a yet unidentified kinase, inhibits the interaction with factor inhibiting HIF-1, thereby preventing hydroxylation and facilitating binding of C-TAD to CBP (41). Thus, multiple direct phosphorylation events appear to regulate the activity of HIF-1␣ at different steps along its activation pathway.…”
Section: Discussionmentioning
confidence: 99%